2023
DOI: 10.3389/fcell.2023.1167626
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on correlations between trace element levels and epilepsy

Abstract: Research investigating the correlation between human trace element levels and disease alterations is growing. Epilepsy, a common nervous system disease, has also been found to be closely related to abnormal levels of trace elements. Studies continue to explore mechanisms of various trace elements involved in epileptic seizures through experimental animal models of epilepsy. Thus, we reviewed the research progress on the correlation between trace element levels and epilepsy in recent years and found that the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
0
0
0
Order By: Relevance
“…Zinc may be involved in the pathogenesis of epilepsy by modulating neuronal excitability. Research also suggested that maintaining zinc balance may have antiepileptic effects, making the maintenance of zinc level a feasible strategy for adjunctive epilepsy treatment [25]. This study also found a negative correlation between serum zinc and epilepsy.…”
Section: Discussionsupporting
confidence: 67%
“…Zinc may be involved in the pathogenesis of epilepsy by modulating neuronal excitability. Research also suggested that maintaining zinc balance may have antiepileptic effects, making the maintenance of zinc level a feasible strategy for adjunctive epilepsy treatment [25]. This study also found a negative correlation between serum zinc and epilepsy.…”
Section: Discussionsupporting
confidence: 67%